Mamluk Cairo, a crossroads for embassies : studies on diplomacy and diplomatics - Bauden, Frédéric; Dekkiche, Malika (Islamic History and Civilization, 2019)
Mamluk Cairo, a Crossroads for Embassies offers an up-to-date insight into the diplomacy and diplomatics of the Mamluk sultanate with Muslim and non-Muslim powers. This rich volume covers the whole chronological span of the sultanate as well as the various areas of the diplomatic relations established by (or with) the Mamluk sultanate. Twenty-six essays are divided in geographical sections that broadly respect the political division of the world as the Mamluk chancery perceived it. In addition, two introductory essays provide the present stage of research in the fields of, respectively, diplomatics and diplomacy. With contributions by Frédéric Bauden, Lotfi Ben Miled, Michele Bernardini, Bárbara Boloix Gallardo, Anne F. Broadbridge, Mounira Chapoutot-Remadi, Stephan Conermann, Nicholas Coureas, Malika Dekkiche, Rémi Dewière, Kristof D'hulster, Marie Favereau, Gladys Frantz-Murphy, Yehoshua Frenkel, Hend Gilli-Elewy, Ludvik Kalus, Anna Kollatz, Julien Loiseau, Maria Filomena Lopes de Barros, John L. Meloy, Pierre Moukarzel, Lucian Reinfandt, Alessandro Rizzo, Éric Vallet, Valentina Vezzoli and Patrick Wing.